What are the best predictors for successful GnRH antagonist protocol in in vitro fertilization (IVF) treatment?. (2nd November 2015) - Samara, Nivin; Reis, Daniel; Danielli Miller, Netanella; Ghetler, Yehudith; Berkovitz, Arie; Miller, Moses; Gonen, Ofer; Shulman, Adrian; Wiser, Amir
Abstract: Objective : To determine factors that affect the success rate of GnRH antagonist protocol in in vitro fertilization (IVF) treatment. Design : Retrospective cohort study. Patients : Patients who underwent IVF cycle with their first GnRH antagonist protocol. Intervention : Antagonist protocol during IVF treatment. The main outcome measurements were; Number of retrieved oocytes, embryo quality and pregnancy rate. Results : Gravidity was negatively correlated with number of eggs ( p  = 0.017), while total follicle number ≥15 ( p  = 0.044) and E2 on day of human chorionic gonadotropin (HCG) ( p  = 0.000) had a positive correlation with number of eggs. Maximum follicle size at HCG administration showed a trend toward an inverse correlation ( p  = 0.053). Addition of LH to drug stimulation was negatively correlated with number of eggs in comparison to rFSH only ( p  = 0.013 and 0.0000, respectively). Age and number of frozen eggs were negatively correlated with successful pregnancy ( p  = 0.025 and 0.004, respectively), while embryo quality, gravidity and number of embryos were positive ( p  = 0.011 and 0.014, respectively). Conclusion : Controlled parameters like timing of antagonist start, duration of antagonist and the optimal leading follicle diameter for HCG triggering had no effect on treatment outcomes. Chinese abstract: 目的：确定在体外受精（IVF）治疗中影响GnRH拮抗剂方案成功的因素。设计：回顾性队列研究。患者：进行IVF周期，第一次应用GnRH拮抗剂方案的患者。干预：IVF中应用拮抗剂方案。主要测定结果：取卵数、胚胎质量和妊娠率。 结果：妊娠与卵子数呈负相关（p = 0.017），然而当总卵泡数≥15个 (p = 0.044) ，注射人绒毛膜促性腺激素（HCG）日的E2 (p = 0.000)与卵子数呈正相关，与注射HCG日最大卵泡大小呈负相关趋势(p =0.053)。药物刺激中添加的LH与卵泡数呈负相关，与rFSH比较只有(分别为p=0.013 、 P=0.0000)年龄和冷冻卵子数与成功妊娠呈负相关(分别为p=0.025 ，p=0.004)，然而胚胎质量，妊娠和胚胎数呈正相关。(p =0.011，p=0.014). 结论：控制的参数如拮抗剂开始的时间，拮抗剂应用的时间和最优的主导卵泡的直径对HCG诱导排卵治疗结局没有影响。